2020
DOI: 10.3390/su12187468
|View full text |Cite
|
Sign up to set email alerts
|

Integrating BIM-Based LCA and Building Sustainability Assessment

Abstract: With the increasing concerns about building environmental impacts, building information modelling (BIM) has been used to perform different kinds of sustainability analysis. Among the most popular are the life cycle assessment (LCA) and building sustainability assessment (BSA). However, the integration of BIM-based LCA in BSA methods has not been adequately explored yet. This study addresses the relation between LCA and BSA within the BIM context for the Portuguese context. By performing an LCA for a Portuguese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…Designers can quickly compare the life cycle impacts and costs of different building elements/envelopes. Additionally, the results of this method are also in line with the sustainability assessment method SBToolPT-H, allowing for the assessment of 3 out of 25 criteria [27,38].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Designers can quickly compare the life cycle impacts and costs of different building elements/envelopes. Additionally, the results of this method are also in line with the sustainability assessment method SBToolPT-H, allowing for the assessment of 3 out of 25 criteria [27,38].…”
Section: Discussionmentioning
confidence: 65%
“…Overall, the LOD 300 has also been identified as the most appropriate to carry out LCA analysis. Typical approaches consist of the collection of LCI data-Bill of Quantities (BoQ)-from BIM to compare the environmental impacts of different solutions in a specific project phase [27]. Nevertheless, Rezaei et al [28] made a BIM-based LCA analysis capable of acting from the project conceptual stage until the design stage.…”
Section: Introductionmentioning
confidence: 99%
“…BIM technologies are used for various aspects of construction life-cycle management such as: assessing building performance for improvement requirements, monitoring all activities throughout the project, optimization of cost and time, using BIM for monitoring the sustainability of buildings with technologies such as IoT solution, developing a 5D BIM model for dynamic monitoring of deep foundation by considering time and cost, and real-time online monitoring of underground space to eliminate errors and difficulties related to this area [ 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 ].…”
Section: Content Analysismentioning
confidence: 99%
“…For example, Švajlenka et al [19] reported the commercial availability of process databases for material and energy flows to improve on the lack of data for LCA. An analysis of state of the art in the integration of LCA with building information modeling (BIM) for data management [20][21][22] highlights many benefits: the integration of BIM-LCA with environmental product declarations (EPDs) for detailed and accurate data for a life cycle inventory [23]; the integration of building LCA and BIM's standard industry foundation classes (IFC) to reduce access barriers and assessment effort/time [24,25]; the comparison of LCAs of buildings with different material structure alternatives [26]. These advantages are the point of departure for assessing the relevance of an exergy-based LCA of buildings.…”
Section: Literature Review: Relevance Of Exergy To a Building Life Cycle Assessmentmentioning
confidence: 99%